An information-based model to assess human cognitive capacity and information processing speed of operators in Industry 4.0. (5th October 2022) - Cavallo, Daniela; Digiesi, Salvatore; Facchini, Francesco; Mummolo, Giovanni
The fourth industrial revolution introduced a new paradigm in manufacturing systems. In the new production environments, operators are supported by new digital technologies, and the physical context is strictly related to the cyber one. In the digital society, recent studies show that individuals have to perform tasks based on the information gathered by a huge amount of data and the operators are employed in more cognitive than physical tasks. Therefore, the purpose of this paper consists in developing an information-based analytical framework to assess the human cognitive capacity occupancy and the human processing time of correct information when the quality performance is known. The model has been tested on case studies. The results show its effectiveness in evaluating the human mental workload imposed by the task performed and the processing speed of correct information with varying quality performance.